2018
DOI: 10.1186/s12944-018-0921-3
|View full text |Cite
|
Sign up to set email alerts
|

Fufang-Zhenzhu-Tiaozhi Capsule reduces restenosis via the downregulation of NF-kappaB and inflammatory factors in rabbits

Abstract: BackgroundTo investigate the effects of a Chinese herbal medicine Fufang-Zhenzhu Tiaozhi Capsule (FTZ) on restenosis and elucidate the mechanism of action.MethodsA restenosis model was established by balloon rubbing the endothelium of the abdominal aorta followed by high fat diet. Rabbits were divided into blank control group, restenosis group, FTZ group (0.66 mg/kg/day), atorvastatin group (5 mg/kg/day) and FTZ + atorvastatin group (n = 8). Vascular stenosis was analyzed by X-ray. Serum levels of chemokines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…This is in line with Zhang et al . (2018) [ 29 ], who report presenting that administration of atorvastatin (5 mg/kg/day) was associated with reduction of all ICAM-1, IL-1β and TNFα in the serum of rabbits, suggesting it has strong anti-inflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with Zhang et al . (2018) [ 29 ], who report presenting that administration of atorvastatin (5 mg/kg/day) was associated with reduction of all ICAM-1, IL-1β and TNFα in the serum of rabbits, suggesting it has strong anti-inflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…In a lot of scientific research, TCM has been widely used to treat and control diabetes and its complications such as renal injury [ 40 ]. The FTZ is an innovative prescription with multiple targets to comprehensively prevent and cure glucolipid metabolic disease [ 34 , 36 ]. FTZ effectively inhibited coronary artery incrassation and protected the myocardium against injury in DM-CHD minipigs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the cardiovascular aspect, FTZ has the cardioprotective effect in the treatment of DM-CHD and diabetic cardiomyopathy (DCM) through inhibiting ERK and STAT3 signal pathways and activating PI3K/AKT pathway [24,49]. Furthermore, recent studies have shown that FTZ reduced restenosis in the rabbit restenosis model by regulating the adiponectin pathway and reducing NF-κB activity [21,22], but the effect of FTZ on vascular endothelium has not been explicit. In this study, we found that FTZ signi cantly inhibited the EndMT of coronary artery in DM-CHD minipigs and revised the reduced cell viability of HUVECs caused by HG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FTZ could inhibit the development of atherosclerosis in the atherosclerosis model and exhibit the cardioprotective effect in the diabetic minipig model with coronary heart disease (DM-CHD) [21][22][23][24]. However, the effect and molecular mechanisms underlying FTZ in DM-CHD are not clear.…”
Section: Introductionmentioning
confidence: 99%